2018
DOI: 10.1002/jcp.26818
|View full text |Cite
|
Sign up to set email alerts
|

Exercise activates the hypothalamic S1PR1–STAT3 axis through the central action of interleukin 6 in mice

Abstract: Hypothalamic sphingosine-1-phosphate receptor 1 (S1PR1), the G protein-coupled receptor 1 of sphingosine-1-phosphate, has been described as a modulator in the control of energy homeostasis in rodents. However, this mechanism is still unclear. Here, we evaluate the role of interleukin 6 (IL-6) associated with acute physical exercise in the control of the hypothalamic S1PR1-signal transducer and activator of transcription 3 (STAT3) axis. Acute exercise session and an intracerebroventricular IL-6 injection increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 37 publications
(79 reference statements)
0
10
0
Order By: Relevance
“…The present study demonstrated that the RHD group also exhibited a decreased S1PR1 expression and an increased STAT3 phosphorylation compared with that in the control group. However, an increase in S1PR1 expression has been reported to increase the phosphorylation of STAT3 ( 23 , 39 ); however, these studies did not examine RHD. Combined with the uncertainty of the expression of S1PR1 in the different heart diseases mentioned above, it can be concluded that the expression of S1PR1 and its role in regulating the phosphorylation of STAT3 in different diseases and different physiological or pathological processes may not be static.…”
Section: Discussionmentioning
confidence: 97%
“…The present study demonstrated that the RHD group also exhibited a decreased S1PR1 expression and an increased STAT3 phosphorylation compared with that in the control group. However, an increase in S1PR1 expression has been reported to increase the phosphorylation of STAT3 ( 23 , 39 ); however, these studies did not examine RHD. Combined with the uncertainty of the expression of S1PR1 in the different heart diseases mentioned above, it can be concluded that the expression of S1PR1 and its role in regulating the phosphorylation of STAT3 in different diseases and different physiological or pathological processes may not be static.…”
Section: Discussionmentioning
confidence: 97%
“…The results of our current study also showed that the RHD group also had down-regulated S1PR1 expression and increased STAT3 phosphorylation level compared to the control group. However, some studies have reported that up-regulation of S1PR1 expression increases the phosphorylation of STAT3 [23,42], but these studies are not about RHD. Combined with the uncertainty of the expression of S1PR1 in different heart diseases mentioned above, it can be concluded that the expression level of S1PR1…”
Section: Discussionmentioning
confidence: 98%
“…This protocol was performed as described previously ( Silva et al, 2014 ; Lenhare et al, 2017 ; Silva et al, 2018 ). Briefly, the mice were acclimated to swimming for 2 days (10 min/24 h).…”
Section: Methodsmentioning
confidence: 99%